2013
DOI: 10.1021/ja310165u
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Enigmatic Mechanism of l-Asparaginase II with QM/QM Calculations

Abstract: In this paper, we have studied the catalytic mechanism of L-asparaginase II computationally. The reaction mechanism was investigated using the ONIOM methodology. For the geometry optimization we used the B3LYP/6-31G(d):AM1 level of theory, and for the single points we used the M06-2X/6-311++G(2d,2p):M06-2X/6-31G(d) level of theory. It was demonstrated that the full mechanism involves three sequential steps and requires the nucleophilic attack of a water molecule on the substrate prior to the release of ammonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 31 publications
6
80
3
3
Order By: Relevance
“…Proposed Direct Displacement Mechanism for gpASNase1-Our inability to prove the existence of a covalent intermediate, together with the residual activity of the threonine mutants support the conclusion made by Gesto et al (15) for the use of a direct displacement mechanism by type I/II L-asparaginases. Based on our crystal structures of the T19A, T116A, and K188M gpASNase1 mutants in complex with Asn, we prepared a schematic of the active site that represents the putative Michaelis complex (Fig.…”
Section: Structural Analysis Of Gpasnase1 Active Site Mutants Fails Tosupporting
confidence: 72%
See 2 more Smart Citations
“…Proposed Direct Displacement Mechanism for gpASNase1-Our inability to prove the existence of a covalent intermediate, together with the residual activity of the threonine mutants support the conclusion made by Gesto et al (15) for the use of a direct displacement mechanism by type I/II L-asparaginases. Based on our crystal structures of the T19A, T116A, and K188M gpASNase1 mutants in complex with Asn, we prepared a schematic of the active site that represents the putative Michaelis complex (Fig.…”
Section: Structural Analysis Of Gpasnase1 Active Site Mutants Fails Tosupporting
confidence: 72%
“…Gesto et al (15) suggested that the covalent intermediate observed in the E. coli T89V structure is an artifact because of the presence of the mutation. We reasoned that we could solve this source of uncertainty by having both threonines present and slowing the reaction (to allow for trapping of the covalent intermediate) by some other active site mutation.…”
Section: Structural Analysis Of Gpasnase1 Active Site Mutants Fails Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Those investigations focused on intersubunit contacts and catalytic loop dynamics to find changes that might increase catalytic rate and enzyme stability. A recent simulation 34 also studied the active site based on the 3ECA structure, which has only 1 water molecule in the active site, resulting in absent networks of hydrogen bonds that stabilize the active site. That paucity of water molecules could be significant.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Enzymatic activity depends on the classic 2-step nucleophilic attack mechanism in E coli ASNase, initiated by WAT1355 and the cooperation of the highly conserved amino acids of Thr12-Tyr25-Glu283 and Ser58-Gln59-Thr89-Asp90-Lys162 from subunit A, and Asn248C and Glu283C from subunit C, respectively, which are interconnected by strong hydrogen bonds. 4,5 The Thr12-Lys162-Asp90 group acts to deprotonate a water molecule (WAT1355) which subsequently binds to the substrate. The second triplet, Thr12-Ty25-Glu283, stabilizes the resulting tetrahedral intermediate.…”
mentioning
confidence: 99%